Spot-Scanning Confocal Photon Beams for Hypofractionated Brain Radiosurgery - Lijun Ma PhD; Shuang Luan PhD; Nguyen Phuong Dang PhD; Benjamin Ziemer PhD; Steve Braunstein MD, PhD; Michael McDermott MD; Cheng Yu PhD; Gabriel Zada MD; Eric L Chang MD (Technology in Cancer Research & Treatment)
Introduction Stereotactic radiosurgery (SRS) has been broadly used to treat brain tumors. In this study, a dose kernel-based spot scanning (DKSC) treatment delivery has been developed for hypofractionated brain SRS. Methods DKSC treatments employs hundreds of confocal photon dose kernels. For such a delivery, a single continuous scanning path was first mapped within a 3D target volume, and then a series of dose kernels of variable sizes, shapes and beam weights were placed and then optimized along the path to produce highly conformal dose distributions. For implementation of DKSC delivery in a clinical setting, we specifically employed the Leksell Gamma Knife (LGK) system, where it is considered as the gold standard of modern SRS treatments. Results DKSC was successfully implemented for a patient treatment for the first time. General methodology as well as specific workflow and treatment planning caveats of implementing DKSC for the LGK is reported. To highlight the novelty of DKSC, we also compared DKSC against the conventional LGK-SRS treatment including its latest treatment planning optimization software. Conclusion DKSC has been demonstrated to be technically feasible, clinically implementable, and uniquely advantageous for hypofractionated brain SRS. Further studies are warranted toward testing DKSC for variable SRS modalities, different disease sites including extra-cranial lesions.